STRATEGI PEMASARAN UMKM SHUTLLECOCK: IMPLEMENTASI BRANDING PRODUK DAN PEMASARAN DIGITAL: Indonesia - Kelly, Estalita; Alamsyah, Moch. Vicky; Hardika, Moch. Bagus; Novitasari, Danis (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The purpose of this community service is to increase community understanding of product branding and digital marketing in improving the economy of Shuttlecock MSMEs in Sumberngepoh village. The method used is the PAR (Participatory Action Research) method. The results of the community service program are to make the MSME community understand the making of brands and digital marketing, can make several logos for shuttlecock brands, are able to do digital marketing by creating accounts on the website and Shopee. This service activity also has an impact on the smooth marketing of shuttlecocks, improving the community's economy and the welfare of the community of Shuttlecock MSME players in Sumberngepoh village.